Oxygen Tension and Blood Flow in Relation to Revascularization in Transplanted Adult and Fetal Rat Pancreatic Islets - Per-Ola Carlsson M.D., Ph.D.; Göran Mattsson (Cell Transplantation, 2002)
We have previously recorded a decreased oxygen tension and blood flow in syngeneically transplanted rat pancreatic islets. The present study related measurements of oxygen tension and blood flow to the vascular density in such grafts implanted beneath the renal capsule. We also evaluated whether transplanted fetal islets are better revascularized than adult islets, and if the degree of revascularization is directly related to the islet vascular endothelial growth factor (VEGF) production. Tissue pO 2 was measured using Clark microelectrodes, whereas islet graft blood flow was measured with laser-Doppler flowmetry. The vascular density of endogenous and transplanted islets was quantified in histological specimens stained with the lectin Bandeiraea simplicifolia (BS-1). Tissue pO 2 in the transplanted adult and fetal islet grafts was similar and markedly lower than in the endogenous islets. The blood perfusion of both the adult and fetal islet grafts was 60–65% of that in the renal cortex. Administration of d-glucose did not affect tissue pO 2 in either the endogenous or transplanted islets, nor graft blood perfusion. The number of capillaries found in the transplanted adult and fetal islets was similar and markedly lower than in endogenous islets. However, in the connective tissue stroma, which constituted ~20% of all islet grafts, the vascular density was higher than in the corresponding endocrine parts of these grafts. Incubated adult islets released higher amounts of VEGF than fetal islets. In conclusion, the previously described low oxygen tension of syngeneically transplanted adult rat islets is related to a low vascular density. Similar low oxygen tension and vascular density are seen in grafted fetal islets. The amount of VEGF production does not correlate to the degree of revascularization of the grafts.